Amino acids and amines stimulate gastrin release from canine antral G-cells via different pathways. - DelValle, J (1990)
The major determinant of meal-stimulated gastric acid secretion is the antral hormone gastrin. Decarboxylated amine derivatives of amino acids have been proposed as the final common mediators of gastrin secretion stimulated by a meal. We explored the cellular basis for this hypothesis using a recently developed isolated canine G-cell model. Both amino acids and, more potently, their corresponding amines, directly stimulated gastrin release. Amino acid-stimulated gastrin secretion was unaffected by decarboxylase inhibitors (alpha methyldopa, aminooxyacetic acid, and 4-deoxypyridoxine) but enhanced by bombesin, isobutylmethylxanthine, and dibutyryl cAMP. Somatostatin inhibited amino acid-stimulated gastrin release via a pertussis toxin-sensitive GTP-binding protein. In contrast, gastrin secretion induced by amines was unaltered by any of the various treatments. Our data indicate that amino acids and amines, either as primary constituents of an ingested meal or as metabolites of dietary proteins, act directly via separate mechanisms to stimulate gastrin secretion from G-cells.